2010
DOI: 10.1002/ase.165
|View full text |Cite
|
Sign up to set email alerts
|

A three‐year prospective longitudinal cohort study of medical students' attitudes toward anatomy teaching and their career aspirations

Abstract: Today's medical students are faced with numerous learning needs. Continuously developing curricula have reduced time for basic science subjects such as anatomy. This study aimed to determine the students' views on the relevance of anatomy teaching, anatomical knowledge, and the effect these have on their career choices. A Likert scale questionnaire was distributed to second year medical students [response rate 91% (n = 292/320)]. The same questionnaire was subsequently distributed to the cohort three years lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 27 publications
(57 reference statements)
2
58
0
1
Order By: Relevance
“…A study inferred that a rationale for early experience would be to strengthen and deepen cognitively, broaden affectively, contextualize, and integrate medical education (Dornan and Bundy, 2004). Another study concluded that vertical integration of anatomy teaching throughout the full medical course may be useful (Bhangu et al, 2010). Knowledge of anatomy is perceived to be important for safe clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…A study inferred that a rationale for early experience would be to strengthen and deepen cognitively, broaden affectively, contextualize, and integrate medical education (Dornan and Bundy, 2004). Another study concluded that vertical integration of anatomy teaching throughout the full medical course may be useful (Bhangu et al, 2010). Knowledge of anatomy is perceived to be important for safe clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…Anatomy education has long been recognized to be important for all areas of medicine (Sugand et al, 2010) and can influence a student's career choice (Bhangu et al, 2010). However, the amount of anatomy teaching included in medical curriculums has declined over the years (Drake et al, 2009), and there is disagreement about how much anatomy is sufficient in a curriculum (Bergman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…4 A cohort study by Bhangu et al showed that 92% of medical students agreed strongly that clinically correlated anatomical teaching was relevant to their clinical practice and helped them during their clinical placements. 5,6 Many felt their preclinical anatomy teaching curriculum had been well taught. However, almost 90% of our respondents stated that anatomy was rarely revisited during their clinical training; neither was it explicitly examined at finals.…”
Section: Discussionmentioning
confidence: 99%